Status mutu air Waduk Jatiluhur dan ancaman terhadap proses bisnis vital - Hamzah Hamzah; M Syamsul Maarif; Marimin Marimin; Etty Riani (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
The Jatiluhur Reservoir is the largest and multipurpose. Indonesia, currently faced with problems regarding the quality and quantity of water resource especially pollution problems. Inthis research has been conducted an analysis of the status of water quality and analysis of their impact on the threat to vital business process, especially with regard to management of water resources. The location research carried out at PerumJasaTirta II as the authority of Jatiluhur Reservoir. The data used in this research is primary data from the obtained field research activities throughthe sampling conducted at Jatiluhur reservoir water and the waters of river basin (DAS) after the Jatiluhur Reservoir outlet with reference to size the parameters of water quality using laboratory quality standard. The Analytical tools used are the method Business Impact Analysis and Storet. Chemical parameters above the quality standard limits are: dissolved oxygen, ferro (Fe), manganese (Mn), zinc (Zn), nitrite (NO2-N), nitrate (NO3-N), sulphate (SO4), chloride (Cl), sulfide(H2S), BOD5, and COD.Condition of water quality can be said to have been classified as heavily polluted (categoryD) byanthropogenic activities that are in the upper reaches of the riverCitarum and around JatiluhurReservoir waters. These conditions can threat and negatively impact vital business of the infrastructure, reservoirs, the availability of drinking water and irrigation water and other water biota.